2021
DOI: 10.1021/acs.jpcc.0c11033
|View full text |Cite
|
Sign up to set email alerts
|

Highly Biaxially Strained Silicene on Au(111)

Abstract: Many of graphene’s remarkable properties arise from its linear dispersion of the electronic states, forming a Dirac cone at the K points of the Brillouin zone. Silicene, the 2D allotrope of silicon, is also predicted to show a similar electronic band structure, with the addition of a tunable bandgap, induced by spin–orbit coupling. Because of these outstanding electronic properties, silicene is considered as a promising building block for next-generation electronic devices. Recently, it has been shown that sil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 48 publications
0
15
1
Order By: Relevance
“…However, presence of the substrate can effectively suppress the PJT effect, and the planar supported form of silicene can exist [10,24,25]. This has been demonstrated in the case of silicene prepared on Au(111) films grown on Si(111) [21,26] and on mica substrates [27].…”
Section: Introductionmentioning
confidence: 93%
“…However, presence of the substrate can effectively suppress the PJT effect, and the planar supported form of silicene can exist [10,24,25]. This has been demonstrated in the case of silicene prepared on Au(111) films grown on Si(111) [21,26] and on mica substrates [27].…”
Section: Introductionmentioning
confidence: 93%
“…46,47 There again, strong interactions with the substrates were demonstrated both theoretically and experimentally. 48,49 More recently, to overcome this limitation various experiments have been carried out on C-based inert substrates such as highly oriented pyrolytic graphite (HOPG) with hexagonal atomic arrangements. [50][51][52][53] On this substrate, the results demonstrated that the charge modulations caused by quantum interferences (QI) serve as templates and guide the incoming Si atoms to self-assemble in 2D clusters.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, the investigations naturally shifted to alternative metal substrates such as Ir(111), Ru (0001), Pt(111), Pb(111), and Au(111). , There again, strong interactions with the substrates were demonstrated both theoretically and experimentally. , …”
Section: Introductionmentioning
confidence: 99%
“…Crystal structure identification of both thin organic and inorganic films, especially two-dimensional (2D) materials beyond graphene, attracts considerable interest, amongst others, in potential electronic applications and pharmaceutical science [1][2][3][4][5][6][7][8][9][10]. The presence of a single crystalline substrate surface during the crystallization process can induce new types of molecular or atomic packing because the substrate tends to act as a template for the crystallization process.…”
Section: Introductionmentioning
confidence: 99%
“…Further, if molecular crystals are epitaxially grown on singlecrystalline substrates, multiple preferred orientations of the adsorbate, several symmetry-related in-plane alignments, and the emergence of unknown polymorphs can occur [17][18][19][20]. For inorganic epitaxial layers also unknown surface-induced polymorphs are frequently observed, such as the formation of a 2D network consisting of so-called blue phosphorene and gold linker atoms [8] or the growth of a strained silicene monolayer on Au(111) [9].…”
Section: Introductionmentioning
confidence: 99%